Predicting Wellness After Pediatric Concussion. (3rd May 2019) - Beauchamp, Miriam H.; Tang, Ken; Yeates, Keith Owen; Anderson, Peter; Brooks, Brian L.; Keightley, Michelle; Désiré, Naddley; Boutis, Kathy; Gagnon, Isabelle; Gravel, Jocelyn; Dubrovsky, Alexander Sasha; Zemek, Roger
Abstract: Objective: Concussion in children and adolescents is a prevalent problem with implications for subsequent physical, cognitive, behavioral, and psychological functioning, as well as quality of life. While these consequences warrant attention, most concussed children recover well. This study aimed to determine what pre-injury, demographic, and injury-related factors are associated with optimal outcome ("wellness") after pediatric concussion.Method: A total of 311 children 6–18 years of age with concussion participated in a longitudinal, prospective cohort study. Pre-morbid conditions and acute injury variables, including post-concussive symptoms (PCS) and cognitive screening (Standardized Assessment of Concussion, SAC), were collected in the emergency department, and a neuropsychological assessment was performed at 4 and 12 weeks post-injury. Wellness, defined by the absence of PCS and cognitive inefficiency and the presence of good quality of life, was the main outcome. Stepwise logistic regression was performed using 19 predictor variables.Results: 41.5% and 52.2% of participants were classified as being well at 4 and 12 weeks post-injury, respectively. The final model indicated that children who were younger, who sustained sports/recreational injuries (vs. other types), who did not have a history of developmental problems, and who had better acute working memory (SAC concentration score) were significantly more likely to be well.Conclusions: Determining the variables associated with wellness after pediatric concussion has the potential to clarify which children are likely to show optimal recovery. Future work focusing on wellness and concussion should include appropriate control groups and document more extensively pre-injury and injury-related factors that could additionally contribute to wellness. ( JINS, 2019, 25, 375–389)